FACTORS INFLUENCING COMPLETION OF IMMUNISATION SCHEDULE AMONG CHILDREN UNDER FIVE YEARS; A CASE OF KOMAMBOGA HEALTH CENTER III; A CROSS-SECTIONAL STUDY. - Ndyamuhaki, Denis; Anywar , Lydia (Student's Journal of Health Research Africa, 2024)
Background The purpose of this study was to examine factors influencing the completion of immunization schedules among children under five years old at Case Komamboga Health Center III. The objectives of the study were; to determine the child-related factors, parent/caretaker, and health facility-related factors influencing the completion of immunization schedule among children below 5 years at Komamboga Health Center III. Methodology The study used a cross-sectional design. Data was collected using a questionnaire method and a questionnaire as a tool. Simple random sampling was used to collect data from the 71 mothers/caretakers. Data was sorted and entered into Microsoft Excel and later presented into pie charts and tables Results The majority (78%) of the respondents had their children immunized however only 56.4% had completed the immunization schedules. The majority of the children that were fully immunized were 12-23 years old (45.1%), were firstborn (32.3%), and were female children (54.8%). Most of the fully immunized children were from the parents/caretakers who were 25-34 years old (61.8%), had secondary education (35.4%), and earned about 100,000-250,000 shillings (41.1%). The majority of the fully immunized children were residing less than 5 kilometers from the health facility (91.7%), and their parents/caretakers stated that the healthcare providers were not friendly (54.8%) and that vaccines were always available (93.5%). Conclusions Generally, child, mother/caretaker, and hospital-related factors influence the completion of immunization schedules among children under five years. Recommendations The study recommends that policies designed to promote child immunization should incorporate age, birth order, distance to health facility, and sex into their policies to have policies impactful.